STUDY OF INFORMATION MANAGEMENT ON PATIENTS AT SUICIDE RISK IN HOSPITAL - Rafi Septiawan Putra (Mount Hope Economic Global Journal, 2024)
The purpose of this study is to study information management against patients at risk of suicide in hospitals. Literary research on how Hospital Information Systems helped improve the efficiency of health services was conducted from 2010 to 2023 using databases such as PUBMED, Sciencedirect, Researchgate, and Google Scholar. For patients who threaten or attempt suicide, success in nursing is characterized by the patient's safe and secure condition. For patients' families who have threatened or attempted suicide the success of nurses is characterised by the family's ability to play a role in protecting family members who are threatening or attempting suicide.